2004
DOI: 10.1016/j.plantsci.2004.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization, essential oil composition and DNA genotyping of Ocimum basilicum L. cultivars

Abstract: The Ocimum genus includes more than 150 species. However, some attributions are difficult, due to the interference of man with selection, cultivation and hybridisation within the genus and to large morphological variation among the different species. A system of standardized descriptors, based on volatile oils, has been proposed, but its use is limited by the fact that several environmental factors may influence the plant chemical composition. In this paper, we experiment the usefulness of molecular markers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(103 citation statements)
references
References 23 publications
5
90
0
8
Order By: Relevance
“…Grayer et al (1996) suggested a combination of major essential oil components rather than a single and dominant compound as a basis of defining chemotypes. Similar argument was pointed out by Labra et al (2004) by mentioning that chemotype determination should not be based on a single essential oil component since plants generally have two or more major compounds of relatively equal amounts. The use of principal component analysis in determining chemotypes has been suggested by Boushama et al (2006) for Lavanduladentata.…”
Section: Discussionsupporting
confidence: 58%
“…Grayer et al (1996) suggested a combination of major essential oil components rather than a single and dominant compound as a basis of defining chemotypes. Similar argument was pointed out by Labra et al (2004) by mentioning that chemotype determination should not be based on a single essential oil component since plants generally have two or more major compounds of relatively equal amounts. The use of principal component analysis in determining chemotypes has been suggested by Boushama et al (2006) for Lavanduladentata.…”
Section: Discussionsupporting
confidence: 58%
“…The biggest differences appeared in the proportion of phosphorus (RAO et al 2007, DZIDA 2010, calcium and magnesium (SEIDLER-£O¯YKOWSKA et al 2009, DZIDA, 2010, and were probably induced by different amounts of mineral nutrients in the nutritional environment of the cultivated plants as well as cultivar-specific differences. The growth dynamics of basil plants, like their morphological characteristics, is highly varied (LABRA et al 2004, NURZYÑSKA-WIERDAK 2007, ABDUELRAHMAN et al 2009, SVECOVA, NEUGEBAUEROVA 2010. The leaf/stem ratio (LS) and the leaf area index (LAI) in basil are significantly affected by both a nitrogen rate (LAI) and a cultivar (LS and LAI) (SIFOLA, BARBIERI 2006), which should also be attributable to the plant's mineral balance.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies show that there are large numbers of species and varieties falls in this genus [1][2][3][4][5] . Several authors recognize more than 60-150 species in the genus.…”
Section: Introductionmentioning
confidence: 99%
“…Regular occurrence of the interspecific hybridization within the genus, have created taxonomic challenges, leaving very little publications on basil taxonomy which follows the International Code of Botanical nomenclature [1,2] . Due to the difficulties in identifying the species, Massimo et al (2004) has concluded that identification can be optimized by combined analysis of morphological traits, essential oil composition and molecular markers [2] . Essential oils are fragrant, highly concentrated essences of plants which are considered to exemplify the soul or life-force of the plant.…”
Section: Introductionmentioning
confidence: 99%